Perceptions of the attractive factors for adopting public–private partnerships in the UAE - Almarri, Khalid (2019)
Public–private partnerships (PPPs) procurement instruments have been very popular tools for developing projects around the world. Through the literature review of peer-reviewed papers, the attractive factors for adopting PPP models were identified. It was warranted to study these factors from a local perspective and triangulate them with the UK factors, which was established as one of the best globally. Through a questionnaire tool, data were collected from 30 participants residing in the UAE and 62 participants residing in the UK. The attractive factors sought after in the implementation of PPP projects were identified to be 13 factors. The attractive factors were further subjected to a multiple regression analysis to establish their influence on the success of PPP projects. The findings show that PPPs are considered to be attractive because they facilitate the transfer of private sector’s skills and experience to the public party, utilize private sector’s funds, add value for money, and transfer risk to the private party. This study contributed to research in the field of PPPs in the UAE and the UK and highlighted the similarities and differences in the practice and opened areas for future consideration.